Outstanding young scientist award in the field of computer science - Sison, Raymund C. (Animo Repository, 2002)
College of Computer Studies Dean Dr. Raymund Sison received the Outstanding Young Scientist Award in the field of Computer Science during the 24th Annual Scientific Meeting of the National Academy of Science and Technology on the theme Enhancing Philippine Science and Technology Thru ICT. The awarding ceremonies were held on July 11 at the Manila Hotel.